A Review of Drama Education among Children. - Too, Sze Yuing; Alizadeh, Farideh; Utama, Indra (AkiNik Publications, 2019)
The concept of utilizing creative drama as a form of education is still relatively new in Malaysia. Nevertheless, the research and effectiveness of drama in education has been proven through the years and there has been a slow introduction and integration within the Malaysian Education system.The theory of this is that drama serves through improving the soft skills of the children from varying communities-by providing them with necessary confidence to elevate esteem. Hence, drama in education stands to be a potentially powerful tool in connecting students with learning and content. To validate this proposition, this literature review examines the impact of drama education in terms of how it could affect the mentality of developing children. It is to understand the deeper psyche to the role drama plays in helping to develop the mental state of children by providing them with the necessary tool beyond basic hard skills. This is conducted with the intent to further understand how the integration of drama education can affect perception of students towards their social status and esteem, also how soft skills education can potentially affect youths in their development for the future. The findings attained from this review,indicates that drama can be deduced as an integral part of the solution that will be able to support students’ development in general.